2002
DOI: 10.1128/jb.184.10.2805-2814.2002
|View full text |Cite
|
Sign up to set email alerts
|

AerR, a Second Aerobic Repressor of Photosynthesis Gene Expression in Rhodobacter capsulatus

Abstract: Open reading frame orf192, which is located immediately upstream of the aerobic repressor gene crtJ, was genetically and biochemically demonstrated to code for a second aerobic repressor (AerR) of photosynthesis gene expression in Rhodobacter capsulatus. Promoter-mapping studies indicate that crtJ has its own promoter but that a significant proportion of crtJ expression is promoted by read-through transcription of orf192 (aerR) transcripts through crtJ. Disruption of aerR resulted in increased photopigment bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…Analysis of ubiquinol oxidase expression indicates that aerR and crtJ mutants exhibit a twofold increase in expression aerobically and no effect anaerobically. This is very similar to the effect on bch, crt, and puc expression that is also observed upon disruption of these regulators (5,8).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Analysis of ubiquinol oxidase expression indicates that aerR and crtJ mutants exhibit a twofold increase in expression aerobically and no effect anaerobically. This is very similar to the effect on bch, crt, and puc expression that is also observed upon disruption of these regulators (5,8).…”
supporting
confidence: 69%
“…Specifically, aerobic repression of ubiquinol oxidase appears to be promoted by the photopigment repressors CrtJ and AerR. These two repressors are known to be responsible for aerobic repression of bacteriochlorophyll, carotenoid, light harvesting, and reaction center gene expression (5,8,17). Our observation that CrtJ and AerR also aerobically repress expression of ubiquinol oxidase (Fig.…”
mentioning
confidence: 56%
“…In contrast, the PpaA homologue from R. capsulatus, AerR (ORF192), was recently reported to function as an aerobic repressor of a subset of PS genes (Dong et al, 2002). In a search for clues regarding PpaA function, we turned to the protein sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For in vivo analysis of disulfide bonds, a strain of Rhodobacter capsulatus was used (ES7 CrtJ-flag) that expressed a chromosomally encoded S-Tag variant of CrtJ (11). Spectral and gel mobility shift data indicated that addition of an S tag at the amino terminus does not affect repressing properties of Crt J (data not shown).…”
Section: Isulfhydryl Alkylation and Thiol Trapping With Amsmentioning
confidence: 99%